Fatigue strength of cable couplers in prestressed concrete beams - Emborg, Mats; Cederwall, Krister; Elfgren, Lennart (Luleå tekniska universitet, Byggkonstruktion och -produktion, 1982)
Fatigue tests have been carried out on ten prestressed concrete beams. Six of the beams were furnished with a cable coupler in the mid-span and four beams had no cable coupler. The uncoupled beams could in some cases sustain 9 times as many load cycles as the coupled beams. Some probable causes to the coupled beams lower fatigue strength are discussed in the paper. Godkänd; 1982; Bibliografisk uppgift: Även publicerad som Teknisk rapport / Högskolan i Luleå, 1983:12; 20061109 (ysko)